Adaptation to a novel host and performance trade‐off in host‐generalist and host‐specific insect ectoparasites. (28th May 2021) - Khokhlova, Irina S.; van der Mescht, Luther; Warburton, Elizabeth M.; Stavtseva, Nadezhda A.; Krasnov, Boris R.
Abstract: We investigated the performance trade‐offs of fleas (Siphonaptera) while adapting to a novel host using two host generalists ( Xenopsylla conformis and Xenopsylla ramesis ) and one host specialist ( Parapulex chephrenis ) maintained on their principal hosts ( Meriones crassus for Xenopsylla and Acomys cahirinus for P. chephrenis ). We asked whether, over generations, (i) a host generalist may become a specialist by evolving the ability to exploit a novel host and losing the ability to exploit an original host and (ii) a host specialist can become a generalist by evolving the ability to exploit a novel host without losing the ability to exploit an original host. We established an experimental line of each species on a novel host ( Acomys russatus for Xenopsylla and M. crassus for P. chephrenis ) and maintained this line on this host during 23 generations. We compared reproductive performance of progenitors of each line and their descendants when they exploited either original or novel host in terms of egg number and size, hatching success, offspring production, and offspring size. We found changes in performance over generations in female offspring size only. Xenopsylla conformis demonstrated a tendency to become a host specialist (increased performance on the novel host with a concomitant decreased performance on the original host), whereas P. chephrenis demonstrated a tendency to become a host generalist (increased performance on the novel host without a concomitant decreased performance on the original host). We conclude that the probability of generalist to specialist transition, and vice versa, is context‐dependent and varies between species.